IMPACT OF FOREIGN CAPITAL ON THE ECONOMIC EFFICIENCY OF FOOD INDUSTRY ENTERPRISES IN THE SLOVAK REPUBLIC - Maroš VALACH (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper is aimed at assessing the economic efficiency of food industry enterprises based on the foreign capital indicator. The decisive emphasis was placed on the hypothesis that, within the economic efficiency of groups of companies with and without foreign capital, companies with foreign capital would be more efficient. This hypothesis was not confirmed in the 2020 calculations, as some enterprises without foreign capital also achieved comparable or better results compared to groups of enterprises with foreign capital. Given that the calculation of the economic efficiency of food enterprises by the method of classifying groups of enterprises was carried out for the first time, we therefore consider the result to be a preliminary finding.